Simple synthesis of rice husk hollow carbon-coated flower ZnO for the anode in a high performance lithium-ion battery - Li, Yi; Huang, Yan; Wang, Xiaofeng; Liu, Weiping; Yu, Kaifeng; Liang, Ce (The Journal of physics and chemistry of solids, 2020)
In this study, a simple hydrothermal method was used to prepare flower-like zinc oxide, which was then combined with biomass hollow carbon derived from rice husk (rice hull cellulose, RHC) under hydrothermal conditions to obtain a ZnO/RHC composite material. The ZnO/RHC composite was used as the anode in lithium-ion batteries and it exhibited excellent electrochemical performance and cycling stability due to its special microstructure. In the ZnO/RHC composite, the sheet structure comprising zinc oxide was coated on the biomass carbon layer of the hollow spherical structure to form numerous conductive networks, thereby improving the electrochemical properties of the ZnO/RHC. The composite provided a reversible specific capacity of 1002.5 mA h g−1 after 160 cycles at 0.2C, which is higher than the theoretical specific capacity of zinc oxide (978 mA h g−1). This material may facilitate the efficient and simple preparation of high performance lithium-ion battery anode materials. A simple hydrothermal method was used to prepare flower-like zinc oxide, which was further combined with biomass hollow carbon derived from rice husk under hydrothermal conditions to obtain ZnO/RHC composite material. When the ZnO/RHC composite was used as anode for lithium-ion batterie, it has exhibited excellent electrochemical performance and cycling stability due to its special micro-structure. [Display omitted] •Simple hydrothermal method used to prepare flower-like zinc oxide.•Flower-like ZnO combined with rice husk-derived hollow carbon to obtain ZnO/RHC.•ZnO/RHC obtained good electrochemical performance as anode in lithium-ion battery.